DAMPAK PENERAPAN KEBIJAKAN HILIRISASI TERHADAP KINERJA KEUANGAN : ANALISIS EMPIRIS PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agesta, Dinda; Nilwan, Afrizal (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the impact of downstream policies on the financial performance of agricultural sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. Using a quantitative approach, this study evaluated six sample companies with secondary data in the form of annual financial statements. The results show that the downstream policy has a positive and significant effect on the company's financial performance, with an average implementation index of 3.94 and an average ROA of 5.64. Regression analysis shows that every increase in one unit of downstream policy increases financial performance by 3,309 units (p < 0.05). The value of the determination coefficient of 21.9% indicates a moderate relationship between the variables. This research emphasizes the importance of investment in technology, product diversification, and government support to maximize downstream benefits. This finding has important implications for the development of agricultural industry policies in Indonesia.